Soil quality evaluation of different land use modes in small watersheds in the hilly region of southern Jiangsu - Ziyi Zhu; Jianyu Chen; Haibo Hu; Meijia Zhou; Yu Zhu; Chaoming Wu; Li Zhu; Xuyi Jiang; Jinlong Wang (Ecological Indicators, 2024)
The Yixing Yuantianjian small watershed is a provincial soil erosion key management area in the hilly region of southern Jiangsu. It has been implemented key national soil erosion control project for small watershed management, which is typical and representative in the region. It is important to quantitatively evaluate the soil quality of the area under different land use modes and then select suitable ecological restoration measures to promote the ecological and economic construction of small watersheds in the hilly region of southern Jiangsu. Used four types of land use (forest land, garden land, arable land and abandoned land) in the Yixing Yuantianjian small watershed as the research object, 13 soil physical and chemical property indicators were screened based on principal component analysis, correlation analysis and Norm value calculation to construct a minimum data set (MDS) for soil quality evaluation. The results showed that the variability of soil chemical indicators of land use modes was higher than that of soil physical indicators in the study area. The MDS indicators affected by soil quality in the small watershed are sand content (Sand), total nitrogen (TN), available nitrogen (AN), available potassium (AK), total soil porosity (TSP) and bulk density (BD), which provide valid information on soil quality in the area with high accuracy. The soil quality index for different land use modes in the small watershed in the hilly areas of southern Jiangsu was SQI forest land (0.83) > SQI cultivated land (0.74) > SQI garden land (0.66) > SQI abandoned land (0.46), with soil quality at a medium to high level. AN was the key factor limiting the soil quality of this watershed. This study can provide a scientific basis for soil quality enhancement and ecological restoration in the small watersheds of the southern Jiangsu hilly region.